Short-term Migration, Rural Public Works, and Urban Labor Markets: Evidence from India. Issue 2 (28th March 2019) - Imbert, Clément; Papp, John
Abstract: This paper studies the effect of India's rural public works program on rural-to-urban migration and urban labor markets. We find that seasonal migration from rural districts that implemented the program decreased relative to those that were selected to, but did not implement it. We use a gravity model and find that real wages rose faster in cities with higher predicted migration from program districts. Since most seasonal migrants work outside of their district, urban wage increases were not limited to program districts, and may have attracted migrants from nonprogram districts. Difference-in-differences may hence be biased. Structural estimates indeed suggest that migration decreased by 22% in program districts, but also increased by 5% in nonprogram districts. As a result, urban wages increased by only 0.5%, against 4.1% if the program had been implemented in all selected districts.